SOCIO-JURIDICAL ANALYSIS OF COMMUNITY PARTICIPATION IN WASTE MANAGEMENT IN GURABESI VILLAGE JAYAPURA CITY - Ramandei, Lazarus; Lamba, Marsal Arung (JURNAL AL-IJTIMAIYYAH, 2024)
This research aims to provide an understanding of community participation-based waste management in Gurabesi Village, Jayapura Utara District, Jayapura City. The main focus is to identify regulations related to waste management, community participation mechanisms, and factors that influence such participation. The type of research used is descriptive qualitative, which aims to describe the phenomena that occur at the research location using socio-juridical analysis. Data collection techniques include interviews, observation, and documentation. Data analysis was conducted using descriptive qualitative techniques. The results showed that one form of community participation in environmental improvement efforts is by donating labor through direct participation. The community also holds meetings to participate directly in waste management. At the RT level, participation tends to be direct, while at the RW level it is more indirect. Based on Arnstein's categories, the level of community participation in Gurabesi Village can be classified at the Informing/Providing Information level. This level of participation is influenced by length of residence, where the longer residents live, the stronger their psychological ties to the environment.This research shows that community-based waste management in Gurabesi Village is not yet optimal, despite the participatory efforts of residents. Improved facilities and infrastructure as well as more intensive socialization on waste management are needed so that community participation can increase and waste management becomes more effective.